2007
DOI: 10.1002/jcb.21563
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1‐phosphate induces EGFR expression via Akt/NF‐κB and ERK/AP‐1 pathways in rat vascular smooth muscle cells

Abstract: Sphingosine 1-phosphate (S1P) has been shown to regulate expression of several genes in vascular smooth muscle cells (VSMCs) and contributes to arteriosclerosis. However, the mechanisms regulating epidermal growth factor receptor (EGFR) expression by S1P in aortic VSMCs remain unclear. Western blotting and RT-PCR analyses showed that S1P induced EGFR mRNA and protein expression in a time- and concentration-dependent manner, which was attenuated by inhibitors of MEK1/2 (U0126) and phosphatidylinositide 3-kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 68 publications
7
41
1
Order By: Relevance
“…AP-1 and NF-B are important transcription factors that play a crucial role in cardiovascular pathophysiology (16,21). To investigate the implication of AP-1 and NF-B in enhanced expression of G q ␣/PLC-␤1 proteins in VSMC from 16-wk-old SHR, we examined the effects of curcumin and helenalin, inhibitors of AP-1 and NF-B, respectively (5,22,36), on the enhanced expression of G q ␣ and PLC-␤1 in VSMC from 16-wk-old SHR. Results shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AP-1 and NF-B are important transcription factors that play a crucial role in cardiovascular pathophysiology (16,21). To investigate the implication of AP-1 and NF-B in enhanced expression of G q ␣/PLC-␤1 proteins in VSMC from 16-wk-old SHR, we examined the effects of curcumin and helenalin, inhibitors of AP-1 and NF-B, respectively (5,22,36), on the enhanced expression of G q ␣ and PLC-␤1 in VSMC from 16-wk-old SHR. Results shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 More recently, we have shown that sphingosine 1-phosphate stimulates ERK1/2 and PI3K/Akt phosphorylation associated with EGFR expression in rat VSMCs. 27 In addition, we have also demonstrated that bradykinin stimulates ERK1/2 activation via transactivation of c-Src and EGFR leading to VSMC proliferation. 28 However, the mechanisms underlying thrombin-induced EGFR expression via transactivation of c-Src/EGFR/PI3K/Akt/ERK1/2 linked to cell proliferation are not completely defined in VSMCs.…”
mentioning
confidence: 93%
“…PCR fragments were analyzed as previously described. 27 These primer sets specifically recognize only the genes of interest as indicated by amplification of a single band of the expected size (502 bp for EGFR and 514 bp for ␤-actin) and direct sequence analysis of the PCR products.…”
Section: Total Rna Extraction and Rt-pcr Analysismentioning
confidence: 99%
“…S1P-induced cell motility is regulated by the p38 MAPK, ERK and Rho pathways in human primary fibroblast-like synoviocytes (Zhao et al, 2008). S1P can also stimulate the activation of PI3K-Akt and ERKs in human dermal MVECs cells (Hsieh et al, 2008;Heller et al, 2008).…”
Section: Introductionmentioning
confidence: 99%